Chronotolerance study of the antiepileptic drug valproic acid in mice - Ben-Cherif Wafa; Dridi Ichrak; Aouam Karim; Ben-Attia Mossadok; Reinberg Alain; Boughattas Naceur A (Journal of Circadian Rhythms, 2012)
Abstract Background Valproic acid (VPA) is an antiepileptic drug widely used for the treatment of absence seizures and generalized tonic-clonic seizures. The present work aims to study whether VPA-induced toxicity varies according to the dosing-time in the 24 hour-scale. Methods The influence of dosing-time on tolerance to VPA was investigated in 120 male Swiss mice synchronized under a light-dark cycle (12:12). The mean VPA lethal dose was first determined to be 850 ± 0.2 mg/kg, i.p.. Such a dose was administered by i.p. route to a total of 90 mice divided in six circadian stages [1, 5, 9, 13, 17 and 21 Hours After Light Onset (HALO)] (15 mice/circadian time); 30 mice were used as control (5 mice / circadian time). Results The surviving treated mice exhibited a significant circadian variation in rectal temperature and body weight loss (p < 0.001). The least rectal temperature change and body weight loss occurred when VPA was injected at 9 HALO. Drug dosing at 9 HALO resulted in -9 % weight loss whereas drug dosing at 17 HALO was -15 % (Ø = 20.3 HALO ± 1.1 h, p ≤ 0.0001). Lethal toxicity also varied according to circadian dosing-time (χ2 = 42.1, p < 0.0001). The highest (60 %) and the lowest (6.67 %) survival rates were observed at 9 HALO and 17 HALO respectively. Cosinor analyses validated a significant circadian rhythm in survival duration with an acrophase at 8.4 HALO ± 0.75 h (p < 0.001). Conclusions With regards to these data the optimal tolerance to VPA occurred when the drug was administered in the second half of the light-rest span of mice which is physiologically analogous to the second half of the night for human patients.